Determination of the X(3872) meson quantum numbers - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review letters, 2013)
The quantum numbers of the X(3872) meson are determined to be JPC=1++ based on angular correlations in B+→X(3872)K+ decays, where X(3872)→π+π−J/ψ and J/ψ→μ+μ−. The data correspond to 1.0 fb−1 of pp collisions collected by the LHCb detector. The only alternative assignment allowed by previous measurements JPC=2−+ is rejected with a confidence level equivalent to more than 8 Gaussian standard deviations using a likelihood-ratio test in the full angular phase space. This result favors exotic explanations of the X(3872) state.